O desenvolvimento da viticultura irrigada na região de Juazeiro - BA e Petrolina - PE: o trabalho na contramão do discurso dominante - Leite, Ângelo Antônio Macêdo (Universidade Federal de São Carlos, 2013)
This work aims to explain the dynamic of the production of fruit in the São Francisco Valley, mainly through the analysis of the working process. Basically, the appreciation and the accumulation of capitals rise from the economic underdevelopment and subordination of the farm workers. Some authors explain the development of fruit and grape production in this region by the local presence of natural characteristics and by its localization. This thesis goes further, and tries to demonstrate how there is a process of modernization of the agriculture in this region, turning subsistence products producer farm workers labour force into free labour force, which to reproduce itself generation after generation, is sold, and, through the sell of labour force, increases the capital value. In the last years, the agriculture production of the region of Juazeiro and Petrolina turned from a subsistence production (typical of the semiarido region) into an entrepreneurial activity, oriented to external high added value markets, based on a complex and advanced productive process and an irrigation system using São Francisco river s water. Some authors explain this new economic dynamics by the rational use of natural and structural resources and undervalue the analysis of man work, that is the core of the analysis, as we consider, the sole work aggregates value to the materials. This search was performed through a qualitative investigation. We interviewed several social actors: land owners, agricultural production managers, consultants and, mainly, land workers. Through their answers we tried to capture the essence of the production dynamics, of their lifestyle and work conditions. The search revealed the dynamic of irrigated fruit production, mainly grapefruit for exportation, is very similar to the industrial one, which aims to control the yield of the workers and the production of capital through the use of new technologies. The development of capitalistic grape fruit production in the region has grown mainly because of the occurrence of six linked processes, besides the others factors presented by other authors: 1- Direct intervention of the State through the development of policies, valorising capitalistic agri-business; 2- Expulsion of small farmers, who produced at subsistence level close to or into the irrigated region; 3- concentration of latifundia in irrigated regions and in close areas; 4- availability and use of local labour force, cheap and subordinate to the capital; 5- use of modern technologies, which enabled the production of grapes varieties to be exported to great food distribution chains; 6- industrial-style oriented management, stimulating the acceleration of working rhythm and the competition among workers.
Keywords: Engenharia de produção; Condições de trabalho; Trabalhadores; Agricultura; Capitalismo; Gerenciamento; Viticultura; Gerenciamento e controle dos trabalhadores; Vale do São Francisco; Workers; Agriculture; Grape culture; Capitalism; São Francisco Valley; Workers management and control; ENGENHARIAS::ENGENHARIA DE PRODUCAO